1999
DOI: 10.1074/jbc.274.30.20925
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Brassinosteroid Biological Activity by a Salicylate-inducible Steroid Sulfotransferase from Brassica napus

Abstract: Recent discoveries from brassinosteroid-deficient mutants led to the recognition that plants, like animals, use steroids to regulate their growth and development. We describe the characterization of one member of a Brassica napus sulfotransferase gene family coding for an enzyme that catalyzes the O-sulfonation of brassinosteroids and of mammalian estrogenic steroids. The enzyme is specific for the hydroxyl group at position 22 of brassinosteroids with a preference for 24-epicathasterone, an intermediate in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
99
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(103 citation statements)
references
References 38 publications
2
99
1
1
Order By: Relevance
“…However, these values are probably not reflecting the real affinity of the enzyme for its substrates, because the assay mixture contained four steroisomers as a result of the presence of two chiral carbons at C-3 and C-7 of the cyclopentanone ring. Substrate-dependent stereoselectivity has been reported for the rat hydroxysteroid and phenol STs and more recently for the B. napus brassinosteroid ST (19,33). Although the stereochemistry of naturally occurring 12-OHJA has not been established unambiguously, naturally occurring 12-OHJA seems to have a cis conformation, and it was shown that cis-12-OHJA has a much stronger tuber-inducing activity than the trans isomer (34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these values are probably not reflecting the real affinity of the enzyme for its substrates, because the assay mixture contained four steroisomers as a result of the presence of two chiral carbons at C-3 and C-7 of the cyclopentanone ring. Substrate-dependent stereoselectivity has been reported for the rat hydroxysteroid and phenol STs and more recently for the B. napus brassinosteroid ST (19,33). Although the stereochemistry of naturally occurring 12-OHJA has not been established unambiguously, naturally occurring 12-OHJA seems to have a cis conformation, and it was shown that cis-12-OHJA has a much stronger tuber-inducing activity than the trans isomer (34).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the fact that JA is not a competitive inhibitor of the reaction indicates that the presence of a hydroxyl group at positions 11 or 12 on the side chain is required for binding at the active site of the enzyme. The strict structural specificity exhibited by AtST2a is a common feature of plant STs and has been observed with the flavonoid, gallic acid glucoside, and brassinosteroid STs (19,37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its levels correlate with the expression patterns of the BR biosynthetic genes BR-6-oxidase and DWARF4 and with the BR synthesis-related P450 genes (Bancos et al, 2002;Shimada et al, 2003). The inactivation of BRs by degradation and conjugation mechanisms contributes to the homeostasis of BRs (Neff et al, 1999;Rouleau et al, 1999;Nakamura et al, 2005;Poppenberger et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…[18,27] The expression pattern of B. napus increased after treatment with salicylic acid and ethanol, which further showed the potential function of these enzymes in the stress response. [18,28] In this paper, we screened a stress tolerance candidate gene OsSOT9 from cultivar Pei'ai 64S (photothermo-sensitive genic male sterile line), which is the maternal parent of the super hybridization rice LiangYou-Pei-Jiu (LYP9) by GeneChip Rice Genome Array and quantitative real-time polymerase chain reaction (qRT-PCR).…”
Section: ¡1mentioning
confidence: 99%